2021
DOI: 10.3390/pharmaceutics13020199
|View full text |Cite
|
Sign up to set email alerts
|

Nebuliser Type Influences Both Patient-Derived Bioaerosol Emissions and Ventilation Parameters during Mechanical Ventilation

Abstract: COVID-19 may lead to serious respiratory complications which may necessitate ventilatory support. There is concern surrounding potential release of patient-derived bioaerosol during nebuliser drug refill, which could impact the health of caregivers. Consequently, mesh nebulisers have been recommended by various clinical practice guidelines. Currently, there is a lack of empirical data describing the potential for release of patient-derived bioaerosol during drug refill. This study examined the release of simul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 26 publications
1
21
0
Order By: Relevance
“…Furthermore, and to ensure safe volumes and pressures are delivered to the patient’s lung on each breath, air leak is minimal, with cuffed endotracheal tubes creating a complete seal within the trachea. This again not only facilitates increased aerosol delivery, but also reduces fugitive medical aerosol emissions to the local environment, and, cognizant of COVID−19, the risk of patient derived transmission of infectious disease [ 55 , 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, and to ensure safe volumes and pressures are delivered to the patient’s lung on each breath, air leak is minimal, with cuffed endotracheal tubes creating a complete seal within the trachea. This again not only facilitates increased aerosol delivery, but also reduces fugitive medical aerosol emissions to the local environment, and, cognizant of COVID−19, the risk of patient derived transmission of infectious disease [ 55 , 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the Schlieren optical system revealed the density gradients in the air and integrated this information in the direction of the optical axis in order to produce a planar image of the respective flow patterns. This flow visualization technique was chosen as it is well established in science and engineering, has been used in infection control research since the late 1960s (Lewis et al, 1969 ; Clark & Edholm, 1985 ; Clark & De Calcina-Goff, 2009 ), and allows 3D flow information to be integrated onto a single plane. Furthermore, the Schlieren optical method does not require the use of any tracer gasses or particles, or high-intensity lasers.…”
Section: Methodsmentioning
confidence: 99%
“…Maintaining a closed pressurized circuit during mechanical ventilation is critical in ensuring the safe ventilation of a patient but also in preventing the release of fugitive medical and patient derived bioaerosol. Joyce et al (2021) used an aerosol particle sizer (APS) to measure the patient derived bioaerosol released from a dual limb mechanically ventilated circuit during nebulizer refill with a VMN and JN. The authors found that there was a significant release of patient derived bioaerosol during refill of the JN, median above ambient levels 710 particles per cm 3 , while levels measured during refill of the VMN were similar to those measured during ambient conditions, median levels above ambient 0 particles per cm 3 .…”
Section: (Iii) (A-c)mentioning
confidence: 99%
“…VMNs have minimal residual drug volume following use and have shown to have increased efficiency for drug delivery; however, no data yet exists demonstrating successful delivery of cells using VMN [102,105]. Nebuliser choice will be somewhat directed through the selection of patient intervention, with some nebuliser types either deemed unsuitable for use during certain interventions, e.g., JN being unsuitable for use during high flow nasal therapy, or delivery will be too low to economically or clinically rationalise its choice [104,[106][107][108][109].…”
Section: Future Prospectsmentioning
confidence: 99%